Tren Penelitian Reintegrasi Sosial pada Klien Pemasyarakatan: Analisis Bibliometrik - Kusumastuti, Wanodya; Japar, Muhammad; Pratisti, Wiwien Dinar; Purwandari, Eny (Universitas Muhammadiyah Metro, 2025)
The high number of recidivism cases is a form of evaluation of the failure of the reintegration process of correctional clients. This study aims to determine the study of reintegration in correctional clients so that further research can be conducted. The research method used is bibliometric analysis using Vosviewer on published articles indexed by Scopus based on searches from 2000-2024. The results of the study showed that a journal search on the scopus.com site with the keywords (reentry OR resettlement OR reintegration*) AND (recidivi OR recidivism*) AND (prisoners OR incarceration OR incarcerated*) obtained 524 journals. Then reduced based on the following aspects, namely (1) English and open access, (2) Scopus-indexed scientific articles, (3) research in 2000-2024, (4) subject areas in the fields of Social, Health and Psychology. Based on the results of the Vosviewer analysis using the co-author method, it shows that the country with the highest reintegration research is America with 390 Scopus-indexed journals. This shows that research interest in the topic of reintegration is very high, followed by Australia and England and other European countries. From the author's context, there are 10 authors who show high frequency in their research, but there are only four authors who are connected to each other. This shows the lack of significant collaboration between authors. In addition, there are several potential variables for further research, namely mental health, well-being, quality of life, self-efficacy, dan support system.